The Management of Innovation - Aghion, P.; Tirole, J. (Quarterly Journal of Economics, 1994)
The paper analyzes the organization of the R&D activity in an incomplete contract framework. It provides theoretical foundations: (a) to understand how the allocation of property rights on innovations may affect both the frequency and the magnitude of these innovations; (b) to rationalize commonly observed features in research employment contracts, such as shop rights, trailer clauses, and the "hired for" doctrine; (c) to discuss the robustness of the so-called Schumpeterian hypotheses to endogenizing the organization of R&D; and (d) to provide a rationale for cofinancing arrangements in research activities.